The Effect of Baseline Length and GSM Network Quality on the Geometric Accuracy of N-RTK Systems - Romi Mitrolia; Sufardi M.S; Muhammad Rusdi (Jurnal Penelitian Pendidikan IPA, 2025)
Network Real-Time Kinematic (N-RTK) positioning has become a fundamental tool in high-precision surveying. However, its accuracy is significantly affected by operational factors, such as baseline length and telecommunication network quality. This research aims to quantify the influence of these two factors on the geometric accuracy of the N-RTK system. Data was collected in a tropical peatland environment in Indonesia. Out of 661 test points, 495 were successfully measured using the N-RTK system with a geodetic GPS. At the other 166 points, however, limited GSM signal coverage in the field necessitated the use of a handheld GPS as an alternative solution to ensure the completeness of the spatial data. The results show that N-RTK accuracy decreases significantly with an increase in baseline length and a decrease in cellular network quality (4G to 3G). The 4G network provides higher accuracy, with a Circular Error 90% (CE90) value of 0.359 m at a 10-20 km baseline distance. At the same distance, the 3G network yields a CE90 of 0.472 m. An increase in distance up to 40-50 km further reduces accuracy, but the resulting accuracy still meets the standard for 1:2500 scale detailed maps. On the other hand, measurements using a handheld GPS yield a CE90 of 5.95 m, which is significantly lower and only suitable for general-scale mapping (1:25,000). This study underscores the importance of cellular network quality and optimal baseline planning to achieve maximum accuracy in N-RTK surveys, as well as highlights the need for alternative solutions in areas with signal limitations.